Quality of liquid goat whey affected by heat treatment of milk and coagulation type: case study of the Serbian market - Miloradovic, Zorana; Hovjecki, Marina; Mirkovic, Milica; Bajcetic, Nikola; Ignjatovic, Ivana Sredovic; Satric, Ana; Smigic, Nada; Maslovaric, Marijana; Jovanovic, Rade; Miocinovic, Jelena (Frontiers in Sustainable Food Systems, 2023)
Two groups of market samples were collected: four samples of whey produced in small scale facilities, and four samples produced in large scale dairy factories. The additional two groups: acid (a) and sweet whey (s) were collected in laboratory from cheeses produced from differently heated goat milk (A - 65°C/30 min, B - 80°C/5 min and C - 90°C/5 min). Gross composition (dry matter content, fat content, protein content), pH, protein, mineral composition and microbial counts were determined. Obtained results for laboratory and market whey samples were analyzed by two-way and one-way ANOVA, respectively. Visualization of quantitative relationships within market and laboratory whey samples has been done by principal component analysis (PCA). Comparison of the protein composition of market samples with those from the laboratory suggested that the majority of goat whey from the market originated from milk heated between 65°C and 80°C. While heat treatment of milk affected protein composition, coagulation type determined mineral composition of whey. The amount of Ca content was almost four times higher, while the amount of Zn is more than 15 times higher in acid than in sweet goat whey. The lack of influence of heat treatment on the Ca and Mg content in whey has been detected. Such behavior is the opposite of cow milk behavior, in which with the subsequent increase in heating temperature, the amount of soluble Ca and Mg decreases. For all analyzed samples, dry matter content was in agreement with the legally required minimum level (5.5%). Although legal requirements for safety and quality of small scale dairy products are more flexible than that of the large counterparts, there was not a single characteristic that differed significantly between small scale and large scale market goat whey.